2003
DOI: 10.1148/radiol.2292020500
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer with Echo-enhanced Contrast Agents: Comparison between Albunex, Optison, and Levovist in Mice—Initial Results

Abstract: Low-intensity ultrasound with echo-enhanced Optison induced efficient gene transfer unlike that with Albunex or Levovist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
129
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(132 citation statements)
references
References 30 publications
2
129
1
Order By: Relevance
“…However, some mice died immediately after receiving an intra-TV injection of Optison even without the sonoporation. Although Optison has been shown to be a useful agent for ultrasound-based transfection in rats and larger animals [9,[12][13][14]17,18], BR14 may be more suitable in mice because a TV injection of BR14 did not kill any mice in the present study. The difference in results may be due to difference in the size of the agents: the mean diameter of BR14 is 2.5-3.0 lm, which is small compared with its predecessors [17,35,36].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, some mice died immediately after receiving an intra-TV injection of Optison even without the sonoporation. Although Optison has been shown to be a useful agent for ultrasound-based transfection in rats and larger animals [9,[12][13][14]17,18], BR14 may be more suitable in mice because a TV injection of BR14 did not kill any mice in the present study. The difference in results may be due to difference in the size of the agents: the mean diameter of BR14 is 2.5-3.0 lm, which is small compared with its predecessors [17,35,36].…”
Section: Discussionmentioning
confidence: 60%
“…The extent of cavitation bubble formation and subsequent increase in membrane permeability can be enhanced by use of microbubble echo contrast agents. This method has been applied to skeletal muscle of mice [9], as well as myocardium of both rats [10] and dogs [11], in vivo, using various microbubble agents including Levovist, Hexabrix, and Optison [9][10][11][12][13][14][15][16][17][18]. It has been indicated that the transfection efficiency is dependent on both the ultrasound parameters and the formulation of microbubbles.…”
mentioning
confidence: 99%
“…25 When compared to similar available agents, Optison was superior for US-mediated gene transfer to skeletal muscle in vivo. 26 A recent study also demonstrated that the effects of US on the cell membrane are much more profound in the presence of Optison, providing further support for the role of cavitation. 27 Thus, we have tested, for the first time, the effect of sonoporation on nonviral gene transfer to the lung.…”
Section: Introductionmentioning
confidence: 86%
“…Alternative clinical echo-contrast agents are now available in Japan. Levovist is one of these agents, although its gene transduction efficacy is reported to be inferior to that of Optison (27). Both are classified as second-generation microbubble agents.…”
Section: Discussionmentioning
confidence: 99%